2019
DOI: 10.1177/0300060519826821
|View full text |Cite
|
Sign up to set email alerts
|

A novel dynamic distraction external fixator for proximal interphalangeal joint fracture dislocation

Abstract: Objective To evaluate the efficacy of a novel dynamic distraction external fixator for proximal interphalangeal joint (PIPJ) fracture-dislocation. Methods From March 2005 to March 2014, 20 patients with PIPJ fracture-dislocation were treated with our technique. Function scores according to the Michigan Hand Outcome Questionnaire (MHQ) score, union time, grip strength, and range of motion (ROM) were recorded before and after treatment. Results All patients completed a mean follow-up of 22 months (range, 12–60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
0
0
3
Order By: Relevance
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Representative previous reports in which more than 20 fingers were affected in acute cases are shown in Table 3 . 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 In acute cases, ROM in this study was comparable with that reported in previous studies. For chronic cases, the number of patients in each study was small, and the time to surgery after injury varied significantly.…”
Section: Discussionsupporting
confidence: 91%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Representative previous reports in which more than 20 fingers were affected in acute cases are shown in Table 3 . 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 In acute cases, ROM in this study was comparable with that reported in previous studies. For chronic cases, the number of patients in each study was small, and the time to surgery after injury varied significantly.…”
Section: Discussionsupporting
confidence: 91%
“…Методика наложения динамического дистракционного аппарата была предложена для лечения внутрисуставных переломов фаланг кисти [6]. Создаваемая ею дистракция достаточна для формирования полости сустава, а также за счет отсутствия жесткого соединения появляется возможность ранней активизации сустава и его разработки в аппарате.…”
Section: материал и методыunclassified
“…Методика выполнения комбинированного лечения контрактур суставов разработана в отделении травматологии № 2 Республиканской клинической больницы, осуществляется следующим образом: под местной анестезией проводится артролиз сустава по ладонной поверхности с целью рассечения спаек передней капсулы, далее через головки проксимальной и дистальной фаланги пальца поперечно проводятся две спицы диаметром 1,2 мм, спицы сгибают на 90° с небольшим отступом от кожи, на выступающих концах спиц формируют крючки, которые соединяются резинками. Методика наложения динамического дистракционного аппарата была предложена для лечения внутрисуставных переломов фаланг кисти [6]. Создаваемая дистракция достаточна для формирования полости сустава, за счёт отсутствия жесткого соединения также появляется возможность ранней активизации сустава и разработки в аппарате.…”
unclassified
“…Изменённые ткани при активизации сустава вклиниваются при сгибании пальца и плотно стягивают фаланги в согнутом положении при попытках разгибания. Данная опера-ция особенно необходима перед наложением динамического дистракционного аппарата и связано это с особенностью устройства, имеющего по одной точке фиксации на каждой фаланге [6]. Вследствие этого при начале тракции палец принимает согнутое положение из-за передней капсулы, которая практически не поддаётся растягиванию.…”
unclassified